Solutions: Trigonometric Formulas and Relationships
Solutions: Trigonometric Formulas and Relationships
Solutions: Trigonometric Formulas and Relationships
Trigonometric
tio
Definition of Ratios
Formulas and Relationships
nS
sin x / cos x = tan x
cos x / sin x = cot x = 1 / tan x
sec x = 1 / cos x
tio
csc x = 1 / sin x
sin2 x + cos2 x = 1
tan2 x + 1 = sec2 x = 1 / cos2 x
lu
tio
sin a + sin b = 2 sin[(a + b)/2] cos[(a - b)/2]
sin a - sin b = 2 cos[(a + b)/2] sin[(a - b)/2]
cos a + cos b = 2 cos[(a + b)/2] cos[(a - b)/2]
sin x sin y = [cos(x - y) - cos(x + y)] / 2
sin x cos y = [sin(x - y) + sin(x + y)] / 2
cos x cos y = [cos(x - y) + cos(x + y)] / 2
lu
cos a - cos b = -2 sin[(a + b)/2] sin[(a - b)/2]
Law of Sines:
So
nS
and the equation reduces to the
Pythagorean Theorem : a2 = b2 + c2
Pythagorean Triples:
tio
x and y are positive integers, x > y :
Let a = x2 + y2 , b = 2xy , and c = x2 - y2
Then a2 = b2 + c2
lu
a sin x + b cos x:
Let q = arctan (- b / a)
Then a [sin x - (- b cos x / a)]
So
nS
tio
lu
So
nS
tio
lu
So
tio
• Length of Arc: s = rθ (θ in radians)
1
• Area of Sector: A = r2 θ (θ in radians)
2
θ
• Angular Velocity: ω = (θ in radians) Linear Velocity: v = =
s rθ
= rω
lu
t t t
• Let (x, y) be a point other than the origin onpthe terminal side of an angle θ in standard position.
We have the following definitions, where r = x2 + y 2 :
x r y r y x
So
nS
• Even: Cosine is an even function, so cos(−x) = cos(x)
• Odd: Sine and Tangent are odd functions, so sin(−x) = − sin(x), tan(−x) = − tan(x).
• Cofunction Identities:
cos(90◦ − θ) = sin(θ), sin(90◦ − θ) = cos(θ), tan(90◦ − θ) = cot(θ), cot(90◦ − θ) = tan(θ),
sec(90◦ − θ) = csc(θ), csc(90◦ − θ) = sec(θ)
tio
• Sum and Difference Identities:
cos(A − B) = cos A cos B + sin A sin B
cos(A + B) = cos A cos B − sin A sin B
lu
tan(A + B) =
1 − tan A tan B
tan A − tan B
tan(A − B) =
1 + tan A tan B
• Double-Angle Identities:
cos(2A) = cos2 A − sin2 A = 1 − 2 sin2 A = 2 cos2 A − 1
sin(2A) = 2 sin A cos A
nS
2 tan A
tan(2A) =
1 − tan2 A
tio
• Half-Angle Identities:
r
A 1 − cos A
sin( 2 ) = ±
2
r
1 + cos A
cos( A2 ) = ±
lu
2
r
1 − cos A 1 − cos A sin A
tan( A2 ) = ± = =
1 + cos A sin A 1 + cos A
So
tio
sin A sin B = [cos(A − B) − cos(A + B)]
2
1
sin A cos B = [sin(A + B) + sin(A − B)]
2
1
cos A sin B = [sin(A + B) − sin(A − B)]
lu
2
• Sum-to-Product Identities:
A+B A−B
So
nS
2 2
A+B A−B
cos A − cos B = −2 sin sin
2 2
• Law of Sines: In any plane triangle ABC, with sides a, b, and c, we have:
tio
a b c
= =
sin A sin B sin C
• Law of Cosines: In any plane triangle ABC, with sides a, b, and c, we have:
lu
a2 = b2 + c2 − 2bc cos A
b2 = a2 + c2 − 2ac cos B
So
c2 = a2 + b2 − 2ab cos C
• Law of Tangents: In any plane triangle ABC, with sides a, b, and c, we have:
A+B
a+b tan 2
nS
= A−B
a−b tan 2
B+C
b+c tan 2
= B−C
b−c tan 2
C+A
c+a tan 2
=
tio
c−a C−A
tan 2
• In any plane triangle ABC, with sides a, b, and c, the area A is given by any of the following:
1 1 1
(a) A = bc sin A = ab sin C = ac sin B
2 2 2
lu
p 1
(b) (Heron’s formula) A = s(s − a)(s − b)(s − c), where s = (a + b + c)
2
So
Z
d
tio
dx
d
dx
d
k=0
[k · f (x)] = k · f 0 (x)
(1)
(2)
Z
dx = x + C
xn dx =
xn+1
n+1
+C
(1)
(2)
lu
(3) Z
dx
dx = ln |x| + C (3)
d x
[f (x)g(x)] = f (x)g 0 (x) + g(x)f 0 (x) (4)
dx Z
ex dx = ex + C
So
d f (x)
g(x)f 0 (x) − f (x)g 0 (x) (4)
= 2 (5)
dx g(x) [g(x)] Z
1 x
d ax dx = a +C (5)
f (g(x)) = f 0 (g(x)) · g 0 (x) (6) ln a
dx Z
d n ln x dx = x ln x − x + C (6)
x = nxn−1 (7)
dx
d
Z
sin x = cos x (8) sin x dx = − cos x + C
nS
(7)
dx
d Z
cos x = − sin x (9)
dx cos x dx = sin x + C (8)
d
tan x = sec2 x (10) Z
dx tan x dx = − ln | cos x| + C (9)
tio
d
cot x = − csc2 x (11)
dx Z
d cot x dx = ln | sin x| + C (10)
sec x = sec x tan x (12)
dx Z
lu
d x
a = ax ln a
Z
(15)
dx sec2 x dx = tan x + C (13)
d 1
ln |x| = (16) Z
dx x csc2 x dx = − cot x + C (14)
d 1
sin−1 x = √ (17)
dx 1 − x2 Z
sec x tan x dx = sec x + C (15)
d −1
nS
cos−1 x = √ (18)
dx 1 − x2 Z
d 1 csc x cot x dx = − csc x + C (16)
tan−1 x = 2 (19)
dx x +1 Z
dx x
d −1 √ = sin−1 + C (17)
cot−1 x = 2 (20) a2 − x2 a
tio
dx x +1
Z
d 1 dx 1 x
sec−1 x = √ (21) = tan−1 + C (18)
dx |x| x2 − 1 a2 + x2 a a
d −1 Z
dx 1 |x|
csc−1 x = √ (22) √ = sec−1 +C (19)
lu
dx |x| x2 − 1 2
x x −a2 a a